Telaah Undang-Undang KUHP Baru dalam Perspektif Politik Hukum - Sonia Desi Rahmawati; Zulkifli Andrian (Pusat Riset dan Inovasi Nasional, 2025)
This study will describe the legal character of the new Criminal Code in the perspective of legal politics, as for the problem in the research, namely how politics is very influential in producing a legal product. this research method uses normative legal research where in this case it examines legal issues and examines norms, as for what is studied in this study is the new Criminal Code Law. This research aims to answer how the politics of law on criminal law reform in indonesia and how the political configuration and legal character of the new Criminal Code. the conclusion of this research is the politics of law in the Criminal Code Update is the politics of criminal law, which is basically a form of policy that responds to the development of human thinking about crime. political configuration that has a major influence on the formation of rules. Legal products that are responsive in character, the process of making them is participatory, which invites as much community participation as possible through social groups and individuals in the community. In relation to the new Criminal Code, it is not responsive or democratic in nature, and it is also born through an authoritarian political configuration because of the lack of popular participation in its design.